2008
DOI: 10.1016/j.rmed.2007.07.023
|View full text |Cite
|
Sign up to set email alerts
|

NT-proBNP is not elevated in patients with obstructive sleep apnoea

Abstract: Our results show by a robust multiple regression analysis, that NT-pro BNP is not associated with OSAS and NT-pro BNP cannot be used as a sensitive marker for underlying cardiovascular abnormalities in patients with OSAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 41 publications
2
25
0
2
Order By: Relevance
“…This phenomena was also observed by Hubner and colleagues, who did not find any association between NTproBNP levels and OSA severity either before or after nasal or bi-level CPAP; however, NT-proBNP levels were associated with impaired left ventricular ejection fraction and systemic arterial hypertension [149]. NTproBNP levels were reduced following nasal CPAP in a handful of patients but this finding was not significant quite possibly due to the small number of patients in this subgroup [149].…”
Section: The Role Of Pap Therapy and Brain Natriuretic Peptidessupporting
confidence: 51%
See 3 more Smart Citations
“…This phenomena was also observed by Hubner and colleagues, who did not find any association between NTproBNP levels and OSA severity either before or after nasal or bi-level CPAP; however, NT-proBNP levels were associated with impaired left ventricular ejection fraction and systemic arterial hypertension [149]. NTproBNP levels were reduced following nasal CPAP in a handful of patients but this finding was not significant quite possibly due to the small number of patients in this subgroup [149].…”
Section: The Role Of Pap Therapy and Brain Natriuretic Peptidessupporting
confidence: 51%
“…Following 1 and 3 months of nCPAP, Tei index decreased in OSA group; and prevalence of GLVD decreased from 19 to 4% [62] Usui et al Hubner et al echocardiography; 28 out of 60 patients were re-evaluated 3 months following PAP treatment NT-proBNP levels were not associated with AHI. Increased NT-proBNP levels correlated with left ventricular ejection fraction, creatinine clearance and arterial hypertension [149] Tasci et al cohort [47], and a 3.5-fold odds of death [24], 6.9-fold odds of cardiovascular related mortality following vascular surgery [24].…”
Section: Brain Natriuretic Peptides As a Marker Of Cardiovascular Rismentioning
confidence: 97%
See 2 more Smart Citations
“…CPAP treatment had no effect on hs-cTnT and NT-proBNP levels in patients without heart failure in both groups despite significant reduction in AHI. In a study by Ljunggren a dose-response relationship between the severity of sleep apnea during the night and the levels of BNP in the morning was seen [27] while other studies found no correlation between OSA severity and NT-proBNP concentration [22,[28][29][30].…”
Section: Polysomnography (Baseline)mentioning
confidence: 99%